1974
DOI: 10.3327/jnst.11.545
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer in Turbulent Separated Flow

Abstract: An investigation was carried out with the object of determining the physical effects of separation and the associated reattachment and redevelopment, upon the heat transfer characteristics of turbulent flow in pipes and to compare the results of these flow conditions with the fully developed one-dimensional condition and with a recently developed numerical technique for the solution of recirculating flows.Separation of the flow was induced in a 4ft length of 2 in. internal diameter nicrome tube of wall thickne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…3C shows a comparison for Nusselt number ratio (Nu x /Nu fd ) against X/H. There is modest agreement between our present data and the data of El-Shazly et al (2005) and Smyth (1974) in the region around the peak of Nusselt number with much good agreement in the redeveloping region after reattachment of the flow. The Nusselt number ratio starts off at approximately two times the fully developed Nusselt number, at entry to the test section, and then rise very steeply peaking at about 3.5 times the fully developed Nusselt number at a point around 7X/H along the test section from the step.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…3C shows a comparison for Nusselt number ratio (Nu x /Nu fd ) against X/H. There is modest agreement between our present data and the data of El-Shazly et al (2005) and Smyth (1974) in the region around the peak of Nusselt number with much good agreement in the redeveloping region after reattachment of the flow. The Nusselt number ratio starts off at approximately two times the fully developed Nusselt number, at entry to the test section, and then rise very steeply peaking at about 3.5 times the fully developed Nusselt number at a point around 7X/H along the test section from the step.…”
Section: Resultssupporting
confidence: 75%
“…For the case of plain pipe expansions, all studies found considerable augmentation of the heat transfer levels with peaks occurring in the vicinity of the reattachment point (Holman, 1984;Zohir and Abdel Aziz, 2006;Krall and Sparrow, 1966;Baughn et al, 1984;El-Shazly et al, 2005;Incropera and Dewitt, 1981;Smyth, 1974). Krall and Sparrow (1966) used an electrically heated stainless steel tube downstream of the orifice, giving them an essentially constant wall heat flux boundary condition.…”
Section: Introductionmentioning
confidence: 96%
“…Smyth [14] conducted experiments to study the physical effects of separation and the associated reattachment and redevelopment, on the heat transfer characteristics of turbulent flow in pipes and compared the results of these flow conditions with the fully developed one-dimensional flow condition. He also compared results with a recently developed numerical technique for the solution of recirculation flows.…”
Section: Heat Transfer To Separation Flow In Heat Exchangers 501mentioning
confidence: 99%